Radio frequency identification based smart parking system using Internet of Things - Atiqur, Rahman (Institute of Advanced Engineering and Science, 2021)
The ideas of shrewd urban communities have consistently been a fantasy. There have been headways produced using the recent years to make a shrewd city dream to reality with the advancement of innovation, smart gadgets are getting increasingly normal in regular daily existence. In this paper a radio frequency identification (RFID) based smart parking system using Internet of Things (IoT) innovation is actualized. The ultrasonic sensors are set before the parking spots and speaker is utilized for sign. On the off chance that the parking space is vacant, at that point light emitting diode (LED) will squint and the parking opening is full LED will be OFF. At the point when vehicle is left the RFID will peruse the data and cut the particular sum and by utilizing IoT location will be sent through short message service (SMS) to proprietor using global system for mobile communications (GSM) and global positioning system (GPS) advancements.